Evaluating the management of building construction material waste in Kurdistan region of Iraq - Agha, Mahmood Muhammed; Ayob, Mohd Fairullazi; Ibrahim, Mohd Shariffuddin (IIUM Press, 2022)
In the construction industry, material waste contributes to a major problem, and the necessity for managing material waste is vital. The main objective of this research is to determine the significant factors that contribute to the construction wastes in the Kurdistan region of Iraq, particularly in the city of Sulaymaniyah. Although, construction and demolition activities have expanded significantly in Kurdistan because of the recent economic development and the growing of cities and urbanisation, but the issues and causes of construction material wastes cannot be neglected. This video presents the outcomes of the study on material waste in the building construction sector with the goal of motivating the performance of managing construction projects in Iraq’s Kurdistan region. The survey questionnaire was the main technique used for conducting and collecting primary data from relevant governmental bodies and construction companies with a study sample of 50 respondents. The result of the analysis demonstrated that the conventional construction method was the most common method utilised for construction. Also, the result illustrated that the main sources and causes of material waste were weak strategy for waste minimisation, lack of staff's awareness on waste management practices, and poor materials storage system. The most wasteful materials were also determined, which included formworks (from timber/wood), tile, sand, and concrete. Apart from that, the result found that possible measures which might contribute to the minimisation of material wastes included the implementation of effective site management and supervision techniques, employing skilled labour, and on-site material storage that is appropriate. In lieu of the findings, this study therefore recommends a necessity to establish a new department of construction waste by the municipalities and ministries. Such effort is expected to enhance policies of waste management and improve effective strategy implementation to minimise construction material waste. This paper follows the other papers that have been presented elsewhere (Mahmood Muhammed Agha, 2021a; Mahmood Muhammed Agha et al. 2021b).